Brain development in a facultatively social allodapine bee aligns with caste, but not group living - Tierney, Simon M.; Jaumann, Sarah; Hightower, Oliver; Smith, Adam R. (Frontiers in Ecology and Evolution, 2025)
IntroductionThe ‘social brain hypothesis’ proposes that brain development (particularly primates) is driven by social complexity, more than group size. Yet, small insects with minute brains are capable of the most complex social organization in animals - which warrants further attention. Research has focused on highly eusocial hymenopterans with extreme caste specialization and very large colony sizes that have passed social evolutionary points of no return. However, facultatively social insects that form small colonies (< 20 individuals) are likely to provide greater insight on brain selection at the origin-point of social group living.MethodsWe undertake the first neurobiological investigation of the facultatively social allodapine bees (Apidae: Xylocopinae: Allodapini), an exploratory study comparing single- and multi-female colonies of Exoneura angophorae. Using volume as a proxy for neural investment, we measured mushroom body calyces, optic lobes, antennal lobes and whole brains of queens, workers, and single-females to test three theories associating brain development with behavior: social brain hypothesis; distributed cognition hypothesis; sensory environment hypothesis.ResultsMushroom bodies were reduced in subordinate workers, but did not differ between queens and single-females. Workers had larger optic lobes than queens, but did not differ from single-females. There were no differences in antennal lobes or whole brain volume.DiscussionSocial caste, rather than multi-female versus single-female nesting, influenced mushroom body volume in this allodapine bee – counter to both social brain and distributed cognition theories and in alignment with halictine and ceratinine bees that also form small facultatively social colonies. Optic lobe enhancement is likely a response to dietary niche requirements for extra-nidal foraging behavior – which may be a highly plastic trait capable of rapid transition among allodapine and ceratinine bees that conforms with ecological intelligence hypotheses. These broad volumetric trends require further investigations on the functional neural circuitry involved in the aforementioned environmental contexts.